Active disturbance rejection control for a pneumatic motion platform subject to actuator saturation: An extended state observer approach - Yuan, Yuan; Wang, Zidong; Yu, Yang; Guo, Lei; Yang, Hongjiu (Automatica (Oxford), 2019)
External disturbances and actuator saturations are two frequently encountered phenomena in pneumatic servo systems. In this paper, a major investigation is carried out on the design of an active disturbance rejection control scheme that is applied to a three-freedom pneumatic motion system subject to actuator saturations. An extended-state-observer (ESO) is proposed to estimate the so-called total disturbance and then an ESO-based composite controller is developed so as to control the pneumatic motion system. With consideration of the actuator saturation effect, a strictly invariant set is estimated for the system under investigation by solving a convex optimization problem via the semi-definite programme method. A number of practical experiments are conducted on a pneumatic motion platform in order to verify the applicability of the proposed method.